Meta-analysis of the expression profiling of miRNAs targeting LRP5 gene in osteoporosis - Sengupta, Mrinmoyee; Das, Mitali (International Journal of Research in Medical Sciences, 2026)
Osteopororsis progressively develops as a consequence of impairment in the complex genetic network and their regulatory elements like miRNAs controlling bone metabolism. Emerging evidence supports that the abnormal expression patterns of some of the miRNAs may offer potentiality as groundbreaking biomarkers. However, the inconsistency in miRNA expression profiling hindered the clinical translation. To bridge this gap, a comprehensive meta-analysis of the expression level of miRNAs targeting particularly the LRP5 gene is conducted aiming to uncover reliable biomarkers that could revolutionize osteoporosis diagnosis and treatment. A systematic literature search was conducted using various databases. Eligible studies comparing miRNA expression between osteoporosis and control subjects in different tissue types through PCR or microarray are selected. Pooled proportions of dysregulated miRNAs were calculated using a random-effects model via the Meta-Analysis Online platform. Heterogeneity was assessed using I² statistics. Robustness was evaluated through sensitivity analyses, including repeated analysis. Studies with ≤10 samples were excluded. This meta-analysis included 15 studies with 916 samples from different continents. The overall pooled proportion of osteoporotic patients with dysregulated circulating miRNAs was 0.50 (95% CI: 0.43-0.57), with substantial heterogeneity (I²=81.5%, prediction interval: 0.21-0.79). Among the most consistently elevated biomarkers were let-7c-3p, miR-23a-3p, miR-23b-3p, and miR-324-3p. miR-23a-3p showed robust upregulation across serum and bone samples in multiple studies, supporting its diagnostic potential. Variation in normalization methods, sample sources, and geographic regions contributed to the higher level of heterogeneity. Sensitivity analyses confirmed the stability of the pooled estimate, and no significant publication bias was detected. Dysregulated miRNAs are significantly associated with osteoporosis. Certain miRNAs show promise as non-invasive biomarkers. Standardized methodologies and broader population-based validation are needed to enhance reproducibility and clinical translation.